Pengaruh Motivasi pada Kinerja Belajar: Pengujian Terhadap Sebuah Model - Nilawati, Levi; Bimo, I. Dwinanto (Universitas Prasetiya Mulya, 2010)
Academic success predictor consists of cognitive measurement, mental intelligence and noncognitive measurement such as personality traits. The desire to accomplish study on time with satisfying achievement is a motivation to study for students. This impetus is a crucial factor for proactive students to attain academic performance. Even if a student has a high intelligence level,without learning motiviation, he or she most likely will fail. Studies of the influence of proactive personality traits on learning performance have received little attention. This research developed and tested a model linking proactive personality to learning performance through a learning motivation by surveying a sample of 272 economics students from a private university in Jakarta. Results from simple regression showed that proactive personality was related to learning performance and learning motivation. Then, learning motivation was related to learning performance. Hierarchical regression analysis demonstrated that learning motivation wasn’t mediating the relationship between proactive personality and learning performance. Future research direction and practical implication (for business) of the result are discussed.